PROFITABILITAS, LEVERAGE, DAN KEBERAGAMAN DEWAN TERHADAP KUALITAS PENGUNGKAPAN SUSTAINABILITY REPORT PADA PERUSAHAAN SEKTOR BASICMATERIAL DAN ENERGI - Noviana Surjati; Synthia Madya kusumawati (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
Companies should not focus on achieving profits without considering the sustainability of the natural and human resources that are the main foundation of their operations. Exploitation of resources without restoration efforts has the potential to cause scarcity, which threatens business continuity. Therefore, sustainability reporting is a crucial instrument to ensure the transparency of a company's preventive and restoration actions. However, not all companies are able to implement sustainable practices due to the high costs involved. Therefore, the decision to disclose a sustainability report is influenced by various internal company factors. This study aims to analyze the influence of profitability, leverage, company size, and board diversity on the quality of sustainability report disclosures in basic materials and energy companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The sample was determined using a purposive sampling method, resulting in 32 companies with a total sample of 96. Data were obtained from the official IDX website and company websites, then processed using SPSS. The results showed that profitability and leverage did not affect the quality of sustainability report disclosures. Conversely, company size and board diversity were shown to have a positive effect on the quality of such disclosures. These findings provide insight into how company characteristics, particularly company scale and board structure diversity, play a significant role in driving transparency of sustainability practices in sectors with high dependence on natural resources..